Pemetaan potensi wisata berbasis ecotourism di Ampelgading: Langkah menuju model wisata ramah lingkungan - Joko Sayono (Universitas Negeri Malang, 2023)
This research was conducted in Ampelgading District, Malang Regency. The objectives of the research were to: (1) explain the concept of ecotourism and its correlation with nature conservation efforts and the empowerment of local communities, (2) identify the socio-economic profile of the region for ecotourism development, and (3) map the potential level of ecotourism development at tourist attractions in the Ampelgading District. This research used a qualitative-descriptive approach and employed observation, interview, and documentation methods for data collection. Data were analyzed using Miles and Huberman-style descriptive analysis. The participants of the research included district and village officials, tourism operators, and business people in the tourism area. The results showed that: (1) there is a strong relationship between ecotourism and efforts to preserve nature and improve the welfare of local communities, (2) the socio-economic conditions of the Ampelgading region support the development of ecotourism, and (3) there is potential for the development of three types of tourism as ecotourism attractions in the Ampelgading region. Penelitian ini dilakukan di Kecamatan Ampelgading, Kabupaten Malang. Tujuan dari penelitian ini adalah untuk: (1) menjelaskan konsep ecotourism dan korelasinya dengan upaya konservasi alam dan pemberdayaan masyarakat lokal, (2) mengidentifikasi profil sosial-ekonomi wilayah untuk pengembangan ecotourism, dan (3) memetakan tingkat potensi pengembangan ecotourism pada obyek-obyek wisata di Kecamatan Ampelgading. Penelitian ini bersifat kualitatif-deskriptif dan menggunakan metode observasi, wawancara, dan dokumentasi untuk pengumpulan data. Analisis deskriptif ala Miles dan Huberman digunakan untuk menganalisis data. Partisipan penelitian ini meliputi perangkat kecamatan dan desa, pengelola pariwisata, dan pelaku usaha di kawasan wisata. Hasil penelitian menunjukkan bahwa: (1) terdapat hubungan yang kuat antara ecotourism dengan upaya pelestarian alam dan peningkatan kesejahteraan masyarakat lokal, (2) kondisi sosial ekonomi wilayah Ampelgading mendukung untuk pengembangan ecotourism, dan (3) terdapat potensi pengembangan tiga jenis wisata di wilayah Ampelgading sebagai objek ecotourism.